Combining Mechanical Fortification and Ultralow Flammability in Epoxy Networks. Issue 2 (10th November 2020) - Saraf, Chinmay; Stubbs, Elizabeth; Hu, Weiguo; Emrick, Todd; Lesser, Alan J.
Abstract: Multifunctional organophosphorus additives present opportunities to engineer epoxy networks with both enhanced mechanical properties and ultralow flammability. This paper describes a systematic investigation of the effect of dimethyl methylphosphonate (DMMP) on the mechanical and heat release properties of both conventional and inherently low flammability epoxy resins. The findings demonstrate that integration of DMMP into epoxy networks produces materials with outstanding flame retardance and increased stiffness. Thermogravimetric analysis of DMMP‐containing networks show that DMMP promotes considerable char formation, with char residue reaching very high levels, up to 55%, for DMMP‐containing deoxybenzoin networks. Microscale combustion calorimetry of all the DMMP‐containing networks exhibit 50% lower heat release capacity and total heat release rate values relative to formulations without DMMP. Moreover, vertical burn tests demonstrate that DMMP‐containing formulations burn slowly and self‐extinguish. Morphological analysis of the charred DMMP‐containing formulations shows a porous structure and mechanical characterization reveals 50% higher elastic modulus, and comparable yield stress, for networks containing DMMP relative to those without DMMP. Overall, this organophosphorus additive represents an opportunity to combine materials chemistry with mechanical enhancement mechanisms to achieve low heat release properties without the need for halogenated flame‐retardant additives. Abstract : Flame retardant, mechanically fortified high T g epoxy networks are realized by use of dimethyl methyl phosphonate in conjunction with both conventional and deoxybenzoin‐based epoxies. Low concentrations of this organophosphorus additive afford self‐extinguishing epoxy networks with high char residue (≈55%), low heat release (≈119 J g −1 K −1 ), and greater elastic modulus.